Pânico: um estudo de interações multiparticipantes em programa radiofônico - Shirlei Maria Freitas de Mello (2007)
From an Interactional Sociolinguistic standpoint, this study aims to describe and to analyze the organization of four broadcast multi-participant interactions and touch upon the interactive dynamics that collaborate for the building of social identities during the talk shows under investigation. Based on Goffmans concept of face (1967), on Brown and Levinsons model of politeness (1987) and on Kerbrat-Orecchionis reflections on polylogues (2004) this research attempts to contextualize the participantsinteractional roles, evidencing the program ethos. It also presents an analysis of the macrostructure of the interactions, their turn-taking and address systems as well as the participation framework. In addition, it deals with the interactive dynamics carried out in an attempt to contribute to the understanding of their rolein the establishment/maintenance of the participants identities in the speech events investigated. The data analysis could reveal a hierarchical organizational pattern in the interactions, under study, which signal the power relations that constitute and regulate the negotiations, carried out by the participants, and which are used to save their faces and sustaintheir public image. Among other aspects, this research could also demonstrate that the analysis of the macrostructure of the interaction, of the participation framework and of the facework carried out are complementary and, co-operatively, help build the ethos of each ofthe interactions.